Analysis Of The Suitability Of Zalora Indonesia's- Commerce Contract With Sharia Principles - Oktapia, Annisa' Suryani; Rozalinda, Rozalinda; Fernanda, Ahmad (Universitas Siliwangi, 2024)
AbstractIntroduction to The Problem: Technological advances, especially the internet, have driven the rapid growth of e-commerce in Indonesia. So, examining the suitability of transactions on platforms such as Zalora with the principles of Islamic sale and purchase contracts is essential.Purpose/Objective Study: This article explores the suitability of the sales and purchase contract in Zalora Indonesia's e-commerce platform with Sharia principles.Design/Methodology/Approach: This research utilizes a qualitative method with an exploratory, descriptive analysis approach. This study's primary and secondary data sources are primary and secondary sources. Primary data sources were obtained directly from participant observation within the Zalora e-commerce application, where the researcher was directly involved as a buyer on Zalora Indonesia's platform. The observed data included the application of contracts in Zalora Indonesia and then comparing their suitability with Islamic contract principles. Secondary sources were taken from books and articles based on the Open Journal System (OJS) regarding contracts and e-commerce. The data obtained will be processed through a framework analysis method, and then the data will be organized into sentences corresponding to the findings. The techniques used in analyzing the collected data include classification, exploration, verification, and conclusion.Findings: The research findings indicate that e-commerce transactions in Zalora, Indonesia, are based on the principles of sales and purchase contracts in Islam. Principles such as godliness, permissibility, honesty, equality, trust, commitment, welfare, keeping promises, willingness and agreement, transparency, and convenience have been applied in e-commerce transactions on Zalora Indonesia's platform..Paper Type: Research ArticleKeywords: Akad; Principle; Zalora Indonesia